Case Report A Comprehensive Rehabilitation Management of Post Operative Idiopathic Adolescent Scoliosis - Didik Febriyanto; Damayanti Tinduh (Indonesian Journal of Physical Medicine & Rehabilitation, 2013)
Objective: Reporting a comprehensive management of physical medicine and rehabilitation of post operative high S curve-idiopathic scoliosis in adolescent.Methods: Patient was assessed for balance contraction of back muscles with biofeedback (BF), chest expansion and endurance capacity with conversed 6 minute walking test (6 MWT) results to metabolicequivalents (METs), pre and post spinal corrective surgery with Harrington’s rod and pedicle screw.Results: Pre and post surgical and rehabilitation integration programs showed improvements in Cobb’s angle (thoracal/lumbar angle was 64o/32o became 20o/5o), chest expansion, spinal muscular balance andstrength, and endurance capacity reflected by METS (5.5; 5.78; and 6.2 respectively).Conclusion: There were improvements in Cobb’s angle, chest expansion, spinal muscular balance and strength, and endurance capacity 6 months post therapy.Keywords: scoliosis, Cobb’s angle, biofeedback, chest expansion, METs